Primulina jingxiensis, a New Record and Confirmation of Loxostigma dongxingensis for the Flora of Vietnam - Uyen, Nguyen Thi To; Thanh, Nguyen Trung; Fang, Wen; Truong, Do Van (VNU Journal of Science: Natural Sciences and Technology, 2022)
We here report Primulina jingxiensis (Yan Liu, W. B. Xu, H. S. Gao) W. B. Xu, K. F. Chung as a new record and confirmed the occurrence of Loxostigma dongxingensis (Chun ex K. Y. Pan) Mich. Möller, H. Atkins for the flora of Vietnam which have been still known endemically to southern China from the previous treatments. Detailed morphological description as Herbs perennial, stemless. Leaves basal, carnose, blades obovate or elliptic to suborbicular, densely villous, thickened, papery when dry, base attenuate to cuneate, apex obtuse to subrounded, margin subentire, lateral veins 2 or 3, inconspicuous. Cymes lax, axillary, 2-5 cymes, 2-4-branched, each 1-3-flowered: bracts 2, opposite, margin entire, pubescent. In addition to the description as color illustrations together with information on distribution, habitat, phenology, and taxonomic notes of these two species are also given.